1992
DOI: 10.1902/jop.1992.63.7.626
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Nd:YAG Laser on in Vitro Fibroblast Attachment to Endotoxin‐Treated Root Surfaces

Abstract: yttrium, aluminum, garnet (Nd:YAG) laser using a 320 micron contact optic fiber handpiece with an energy setting of 80 mJ at 10 pulses per second for one minute.The fiber was held perpendicular to the root surface. An attempt was made to cover the entire root surface equally during the one minute of exposure. This was confirmed in a subsequent pilot study using lased, non-diseased root segments.A pilot study using photoacoustic spectroscopy on a iii laser charred root surface revealed the presence of a charged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
2
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 33 publications
1
68
2
1
Order By: Relevance
“…The Nd:YAG laser application reported by some investigators exhibited, under SEM analysis, surface alterations such as charring, crater formation, and cement meltdown. 38,[46][47][48][49][50][51][52][53][54] Studies with Nd:YAG laser using different parameters 47,48 have shown that mean power settings ranging between 1.25-3.00 W promote a root surface change leading to fusion and resolidification of the cement mineral portion alongside crack and fissure formation. Thomas et al 46 reported that the Nd:YAG laser denatures root surface proteins, and they suggest that the complement of the conventional mechanical treatment of the root surface would be important on the reduction of these irregularities aiming for a more biocompatible root surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nd:YAG laser application reported by some investigators exhibited, under SEM analysis, surface alterations such as charring, crater formation, and cement meltdown. 38,[46][47][48][49][50][51][52][53][54] Studies with Nd:YAG laser using different parameters 47,48 have shown that mean power settings ranging between 1.25-3.00 W promote a root surface change leading to fusion and resolidification of the cement mineral portion alongside crack and fissure formation. Thomas et al 46 reported that the Nd:YAG laser denatures root surface proteins, and they suggest that the complement of the conventional mechanical treatment of the root surface would be important on the reduction of these irregularities aiming for a more biocompatible root surface.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al 46 reported that the Nd:YAG laser denatures root surface proteins, and they suggest that the complement of the conventional mechanical treatment of the root surface would be important on the reduction of these irregularities aiming for a more biocompatible root surface. Meanwhile, Trylovich et al 49 found that Nd:YAG laser application modifies biocompatibility of root surfaces and reduces the number of attached fibroblasts in comparison with untreated controls. Their study suggested that Nd:YAG laser could alter the biocompatibility of the cementum surface, making it unfavorable for fibroblast attachment.…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Periodontology, in its position statement on lasers in ENAP, 15 states 'The Academy is not aware of any published data that indicates that the ENAP laser procedure is any more effective for these purposes than traditional scaling and planing'. 12,[16][17][18][19][20][21][22] This is sharply contrasted by reports by Gregg and McCarthy, reported in later journals. [23][24][25] In 2004 in a study presented by Evans 26 to review the new attachment procedure on a sample of six cases, evidence was given to show new cementum and bone growth, including periodontal ligament.…”
Section: De-epithelialisation Of the Periodontal Pocketmentioning
confidence: 85%
“…Of these, the Nd:YAG laser was reported to be the most effective [5], even though some difficulties were experienced in achieving homogeneous results. The Nd:YAG laser has also been used for a wide range of other dental applications, including root planing [6], altering fibroblast attachment [7], apical sealing [8], treatment of hypersensitivity [9], removal of smear layer [10], soft tissue surgery [11], and ablation of hard tissue [12].…”
Section: Introductionmentioning
confidence: 99%